Pengaruh Komitmen Organisasi Dan Motivasi Kerja Terhadap Perilaku Menyimpang Dengan Gaya Kepemimpinan Sebagai Variabel Moderating Pada Kantor Pertananahan Kota Bukittinggi - Hisa Bena, Boy (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
This study aims to analyze deviant behavior at the Land Office of Bukittinggi by looking at the effect of organizational commitment variables on deviant behavior and the effect of work motivation on deviant behavior by using leadership style as a moderating variable.This type of research is a comparative causal research. The population in this study were all employees of the Land Office of Bukitinggi City from all sub-sections of the agency totaling 43 people. In this study, the census method was used, namely by giving questionnaires to the entire population of 43 people consisting of all employees of the sub-department of the agency. The data analysis technique in this study uses SEM (Structural Equation Modeling) analysis which is operated based on Partial Least Square (PLS) with the SmartPLS 3.0 tool. The results of the study indicate that the organizational commitment variable has a positive and significant effect on deviant behavior which is strengthened by the leadership style, work motivation has a positive and insignificant effect on deviant behavior which is weakened by the leadership style. reduce deviant behavior that occurs in the Bukittinggi City Land Office environment.